2007
DOI: 10.1007/s12098-007-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of permethrin cream and oral ivermectin in treatment of scabies

Abstract: Mass treatment of scabies with ivermectin in an endemic population is more efficacious as compared to topical permethrin application in reducing the baseline prevalence, decreasing the chain of transmission and chances of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…[20] A recent trial proved that ivermectin significantly decreased post-treatment reinfestation as compared to permethrin, but the cause remained obscure. [25] On the basis of such results many researchers, regulatory bodies, and WHO recommend ivermectin use for mass treatment of scabies. [26] Ivermectin cannot be the best drug in every hospital setting; in spite of showing promise in its efficacy and safety, as the local resistance pattern (which we did not find) and the affordability of patient population varies, and other cheaper alternatives still have an important role in marginalized economies.…”
Section: Discussionmentioning
confidence: 99%
“…[20] A recent trial proved that ivermectin significantly decreased post-treatment reinfestation as compared to permethrin, but the cause remained obscure. [25] On the basis of such results many researchers, regulatory bodies, and WHO recommend ivermectin use for mass treatment of scabies. [26] Ivermectin cannot be the best drug in every hospital setting; in spite of showing promise in its efficacy and safety, as the local resistance pattern (which we did not find) and the affordability of patient population varies, and other cheaper alternatives still have an important role in marginalized economies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, ivermectin is not available in Iraq, so treatment with topical permethrin is suggested. The reported clinical trials on the use of oral ivermectin indicate that the drug is an effective and practical agent in the control of scabies [7,27,28]. In order to control scabies and to prevent its further spread, improvements in health care delivery are of vital importance now in Iraq.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of disease is highest in tropical countries, where scabies is endemic [1]. Epidemiological studies worldwide have suggested a 7-to 28-year cyclic pattern of disease prevalence [2][3][4][5][6][7][8]. Scabies is particularly common in resource-poor communities with crowded living conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a semi synthetic macro cycleclic lactone antibiotic agent. Some studies showed that it is safe and effective in the treatment of scabies [13][14][15] . Ivermectin is a novel antiparasitic agent effective against a variety of endoparasites and ectoparasities.…”
Section: Introductionmentioning
confidence: 99%